2014
DOI: 10.18632/oncotarget.2786
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor 1 alpha is regulated by RBM38, a RNA-binding protein and a p53 family target, via mRNA translation

Abstract: Hypoxia-inducible factor 1 (HIF1), a heterodimeric transcription factor, consists of HIF1α and HIF1β and is necessary for cell growth and survival under a hypoxic condition. Thus, the level and activity of HIF1α needs to be tightly controlled. Indeed, HIF1α protein stability is controlled by prolyl hydroxylase and von Hippel-Lindau-mediated proteosomal degradation. However, it remains unclear whether HIF1α expression is controlled by other pathways. Here, we showed that RNA-binding protein RBM38, a target of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…36 A very interesting example of the potential role of RNA-protein interaction in the response to hypoxia is the targeting of specific mRNAs to polysomes for translation via the 59 cap binding of the HIF2a-RBM4-eIF4E2 complex. 37,38 Furthermore, key aspects regarding hypoxia are cellular metabolic adaptations (e.g., activation of glycolysis) and recent work has suggested that a large number of metabolic enzymes possess RNAbinding capacity. 2,3 Interestingly, a significant number of enzymes involved primarily in glucose handling in the kidney were identified as RBPs either by our RIC screen or previously published data 3 (Supplemental Figure 5A).…”
Section: Discussionmentioning
confidence: 99%
“…36 A very interesting example of the potential role of RNA-protein interaction in the response to hypoxia is the targeting of specific mRNAs to polysomes for translation via the 59 cap binding of the HIF2a-RBM4-eIF4E2 complex. 37,38 Furthermore, key aspects regarding hypoxia are cellular metabolic adaptations (e.g., activation of glycolysis) and recent work has suggested that a large number of metabolic enzymes possess RNAbinding capacity. 2,3 Interestingly, a significant number of enzymes involved primarily in glucose handling in the kidney were identified as RBPs either by our RIC screen or previously published data 3 (Supplemental Figure 5A).…”
Section: Discussionmentioning
confidence: 99%
“…RBPs like Y‐box binding protein 1 (YB‐1) , Hu antigen R (HuR) , polypyrimidine tract binding protein (PTB) , and cold‐inducible RBP (CIRBP) are able to increase the stability of the HIF1α mRNA followed by elevated protein synthesis. On the other hand, tristetraprolin (TTP) RBP family , RNA binding motif protein 38 (RBM38) , and cytoplasmic polyadenylation element binding proteins 1 and 2 (CPEB1 and CPEB2) bind to the 3′ UTR of the HIF1A mRNA leading to decreased translation. In the 5′ UTR of the HIF2A mRNA, iron‐responsive elements (IREs) are present.…”
Section: The Structure and Physiology Of Hypoxia‐inducible Factorsmentioning
confidence: 99%
“…When DNA has sustained damage, p53 expression can be stimulated and then can activate DNA repair proteins, including MSH2 (21), ERCC6 (22), RBM38 (23), and p21 (24) (Fig. 2B).…”
Section: Significancementioning
confidence: 99%
“…RBM38 is a target of p53 and a negative regulator of p53 and MDM2 (26). Interestingly, RBM38 is required for maintaining the stability of the basal and stress-induced p21 transcript (27) and also regulates HIF1α expression via mRNA translation (23). MSH2 is a caretaker gene that is responsible for DNA mismatch repair and is involved in many different forms of DNA repair, including transcription-coupled repair (28), homologous recombination (29), and BER (30).…”
Section: Significancementioning
confidence: 99%